Research on Maximum Likelihood Decoding Algorithm and Channel Characteristics Optimization for 4FSK Ultraviolet Communication System Based on Poisson Distribution - Li Kuang; Yingkai Zhao; Kangjian Li; Xingfa Wang; Linyi Li; Huishi Zhu; Weijie Zhang; Jianguo Liu (Photonics)
This study focuses on a 4FSK-modulated ultraviolet (UV) communication system, introducing an innovative symbol-level maximum likelihood decoding approach based on Poisson statistics. A forward error correction (FEC) coding mechanism is integrated to enhance system robustness. Through Monte Carlo simulations, the proposed decoding scheme and the error correction performances of Reed–Solomon (RS) and Low-Density Parity-Check (LDPC) codes are evaluated in UV channels. Both RS and LDPC codes significantly improve the Bit Error Rate (BER), with LDPC codes achieving superior gains under low SNR conditions. Hardware implementation and field tests validate the decoding algorithm and LDPC-optimized 4FSK system. Under non-line-of-sight (NLOS) conditions (10–45° transmit elevation angle), stable 60 m communication with BER < 10−3 is achieved. In line-of-sight (LOS) scenarios, the system demonstrates 900 m range with BER < 10−3, highlighting practical applicability in challenging atmospheric environments.